Pengaruh Model Pembelajaran Poew (Predict, Observe, Explain And Write) Terhadap Prestasi Belajar Fisika: Influence of POEW (Predict, Observe, Explain and Write) Learning Model on Physics Learning Achievement - Ni’mah, Ummi Lailatun; Prihatni, Yuli (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study aims to determine the trend of physics learning achievement using the POEW learning model and conventional learning descriptively. The influence of the POEW learning model on physics achievement is known comparatively. This research is a quasi-experiment. The population of the study consists of the eighth-grade students of MTs Mathali'ul Huda Pati for the 2013/2014 academic year. There are 110 students in the class. Random sampling was used to obtain a sample of 74 students. Based on test results from 30 questions, 26 questions were valid, and 4 questions were invalid. An rtt of 0.877 was used to determine the reliability of the instrument. Data analysis includes prerequisite analysis tests, normality tests of distribution, and homogeneity tests of variance. The results showed that the trend of physics learning achievement using the POEW model falls into the high category, while the conventional model falls into the moderate category. In the t-test, obtained t count = 3.565 and p = 0.001, which means the hypothesis is accepted by students and is significant. There is a significant difference in physics learning achievement using the POEW model and the conventional model. Therefore, there is an influence of the use of the POEW model on physics learning achievement.